Lidská prionová onemocnění v České republice - Rohan, Z; Rusina, R; Marešová, M; Matěj, R (Epidemiologie, mikrobiologie, imunologie, 2015)
Human prion diseases are a group of very rare diseases with a unique pathogenesis and, due to an inauspicious prognosis and unavailability of therapy, with fatal consequences. The etiopathogenetic background is the presence of pathologically misfolded prion protein, highly resistant to denaturation, the aggregation and presence of which in the brain tissue causes irreversible neuronal damage. The most frequent prion disease in humans is Creutzfeldt-Jakob disease (CJD) which occurs in sporadic, hereditary/familial, or acquired/infectious/iatrogenic forms. A new form of CJD, variant CJD, is considered to be linked to dietary exposure to beef products from cattle infected with bovine spongiform encephalopathy (BSE) and to infection via blood transfusion. The clinical picture of these diseases is characterized by a rapidly progressing dementia, cerebellar and extrapyramidal symptoms, and rather specific MRI, EEG, and CSF findings. Clinically, the diagnosis is described as possible or probable prion disease and needs to be confirmed by neuropathological or immunological investigation of the brain tissue. Epidemiological data from the Czech Republic spanning the last decade are presented.
Keywords: Cattle; Animals; Česká republika; skot; potransfuzní reakce; Humans; nemoci skotu; lidé; Transfusion Reaction; zvířata; Cattle Diseases; encefalopatie bovinní spongioformní; Creutzfeldt-Jakob Syndrome; Czech Republic; Encephalopathy, Bovine Spongiform; Creutzfeldtova-Jakobova nemoc